(3eHGQb GdCRgGQ aj TQM eTGQb GdCfhGQs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc , (B801 (3g`s ((3YHO Gddg Hf GdMGL YKeGf GdKQhjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi gOjI GdgOGjI hGdESdGe hHYO jbhd GdYHO GdYhjR YHO GddWja Hf YHO GdYRjR GdeYQha HGHf edc hef CaVdg Yde GdCMGOjK heeG Ufa ajg ef GdcJH GdaGNQI eTGQb GdCfhGQ hCSJNjQ Gddg Cf CTQMg TQMG jNHQ Yf NHGjG OcJ (B( (3cPG (B) (3YHGQJg hSejJg eHGQb GdCRgGQs
(3BNQgG (B:s
(3heYfi GdKGfj JYdjd Hbhdg (B: (3dHjc cGf jdHj HgPg GdJdHjI aj MLHJg hYeQJg CfS QVj Gddg JYGdi Yfg Qhi eSde Yfg dHjc YeQI hMLG efUhHI HebOGQ Cj eQOjG YeQI Ch HfRY GdNGaV Cj HYeQI gPG jOd Ydi Cfg Ydjg GdSdGe cGf bGQfG JbOe GdcdGe heGgh (B( (3cPG CUM GdQhGjGJ GdhGQOI ajg aj Chd GdHGH GdJGSY (B)s
(3Chdg agQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 59s
(3eYLe GdeDdajf (B2 / 215s
(3cTa GdXfhf (B2 / 1689s
(3TPQGJ GdPgH (B7 / 342s
Keywords: (3GdMOjK hGdeUWdMs